Spontaneous ejaculation in a wild Indo-Pacific bottlenose dolphin (Tursiops aduncus). - Tadamichi Morisaka (Public Library of Science (PLoS), 2013)
Spontaneous ejaculation, which is defined as the release of seminal fluids without apparent sexual stimulation, has been documented in boreoeutherian mammals. Here we report spontaneous ejaculation in a wild Indo-Pacific bottlenose dolphin (Tursiops aduncus), and present a video of this rare behavior. This is the first report of spontaneous ejaculation by an aquatic mammal, and the first video of this behavior in animals to be published in a scientific journal.